Affecting HEK293 Cell Growth and Production Performance by Modifying the Expression of Specific Genes - Laura Abaandou (Cells, 2021)
The HEK293 cell line has earned its place as a producer of biotherapeutics. In addition to its ease of growth in serum-free suspension culture and its amenability to transfection, this cell line’s most important attribute is its human origin, which makes it suitable to produce biologics intended for human use. At the present time, the growth and production properties of the HEK293 cell line are inferior to those of non-human cell lines, such as the Chinese hamster ovary (CHO) and the murine myeloma NSO cell lines. However, the modification of genes involved in cellular processes, such as cell proliferation, apoptosis, metabolism, glycosylation, secretion, and protein folding, in addition to bioprocess, media, and vector optimization, have greatly improved the performance of this cell line. This review provides a comprehensive summary of important achievements in HEK293 cell line engineering and on the global engineering approaches and functional genomic tools that have been employed to identify relevant genes for targeted engineering.